Identification of PANoptosis-relevant subgroups to evaluate the prognosis and immune landscape of patients with liver hepatocellular carcinoma - Zhang, Zhengwei; Zhang, Feng; Pang, Ping; Li, Yapeng; Chen, Xiaoning; Sun, Shibo; Bian, Yu (Frontiers in Cell and Developmental Biology, 2023)
Liver hepatocellular carcinoma (LIHC), one of the most frequently seen malignancies, is difficult to be diagnosed at an early stage with its prognosis extremely poor. Despite the fact that PANoptosis is of importance in the occurrence and development of tumors, no bioinformatic explanation related to PANoptosis in LIHC can be found. A bioinformatics analysis on the data of LIHC patients in TCGA database was carried out on the basis of previously identified PANoptosis-related genes (PRGs). LIHC patients were divided into two PRGs clusters whose genes characteristics of differentially expressed genes (DEGs) were discussed. According to DEGs, the patients were further divided into two DEGs clusters, and prognostic-related DEGs (PRDEGs) were applied to risk score calculation, the latter of which turned out to be practical in identifying the relationship among risk score, patient prognosis, and immune landscape. The results suggested that PRGs and relevant clusters were bound up with survival and immunity of patients. Moreover, the prognostic value based on two PRDEGs was evaluated, the risk scoring model constructed, and the nomograph model for predicting the survival rate of patients further developed. Therefore, it was found that the prognosis of the high-risk subgroup was poor. Additionally, three factors, including the abundance of immune cells, the expression of immune checkpoints, immunotherapy and chemotherapy were considered to be associated with the risk score. RT-qPCR results indicated higher positive expressions of CD8A and CXCL6 in both LIHC tissues and most human liver cancer cell lines. In summary, it was suggested that PANoptosis was bound up with LIHC-related survival and immunity. Two PRDEGs were identified as potential markers. Thus, the understanding of PANoptosis in LIHC was enriched, with some strategies provided for the clinical therapy of LIHC.